2001
DOI: 10.1111/j.1469-8749.2001.tb00156.x
|View full text |Cite
|
Sign up to set email alerts
|

Autistic disorders in Down syndrome: background factors and clinical correlates

Abstract: A study of a clinic-based sample of 25 individuals (12 females, 13 males; age at diagnosis 14.4 years, SD 7.4 years; age range 4 to 33 years) with Down syndrome (DS) and autism spectrum disorders, demonstrates that autism is by no means rare in DS. Results showed that there was a considerable delay in the diagnosis of autism as compared with children with autism who did not have DS. In 11 participants medical factors were identified that were likely to be of importance in contributing to the development of aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
1
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 18 publications
2
24
1
1
Order By: Relevance
“…1). Tentative diagnosis reflected the reality facing clinicians, as sometimes it is difficult to diagnose autism in young children, for instance when they also have a substantial developmental delay and/or a medical condition/syndrome, and/or when the results of diagnostic instruments do not converge (Lord, 1995;Nordin & Gillberg, 1996;Rasmussen, Bö rjesson, Wentz, & Gillberg, 2001). It has been suggested that in cases of suspected autism no children below 3 years of age should receive other than a tentative PDD diagnosis, which should be reviewed when they are 5-6 years of age (Szatmari, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…1). Tentative diagnosis reflected the reality facing clinicians, as sometimes it is difficult to diagnose autism in young children, for instance when they also have a substantial developmental delay and/or a medical condition/syndrome, and/or when the results of diagnostic instruments do not converge (Lord, 1995;Nordin & Gillberg, 1996;Rasmussen, Bö rjesson, Wentz, & Gillberg, 2001). It has been suggested that in cases of suspected autism no children below 3 years of age should receive other than a tentative PDD diagnosis, which should be reviewed when they are 5-6 years of age (Szatmari, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Children with Down syndrome and ASD had lower IQ's, and more severe, odd stereotypic behaviors, anxiety, and social withdrawal. Others find that risk factors for autism in children with Down syndrome include such medical conditions as seizures, early hypothyroidism, postcardiac surgery complications, as well as having lower IQ's and first or second degree relatives with ASD or with the broader autism phenotype [Ghaziuddin, 2000;Rasmussen et al, 2001;Starr et al, 2005].…”
Section: Childrenmentioning
confidence: 97%
“…4,5 Autism is also being diagnosed with increasing frequency in individuals with Down syndrome. 6,7 This co-occurrence has been reported to occur at a rate of at least 7% in individuals with Down syndrome. 8 However, because of the developmental delays that are inherent with a diagnosis of Down syndrome, practitioners may be hesitant to make the second diagnosis of autism even when full diagnostic criteria for autism have been met.…”
mentioning
confidence: 96%